Body Mass Index, Abdominal Fatness, and Heart Failure Incidence and Mortality: A Systematic Review and Dose–Response Meta-Analysis of Prospective Studies. Issue 7 (16th February 2016) - Aune, Dagfinn; Sen, Abhijit; Norat, Teresa; Janszky, Imre; Romundstad, Pål; Tonstad, Serena; Vatten, Lars J.
Abstract : Background—: Obesity has been associated with increased risk of heart failure, but whether overweight also increases risk is unclear. It is also unclear whether abdominal adiposity is more strongly associated with heart failure risk than general adiposity. We conducted a systematic review and meta-analysis of prospective studies to clarify the strength and shape of the dose-response relationship between general and abdominal adiposity and the risk of heart failure. Methods and Results—: PubMed and Embase databases were searched up to October 10, 2014. Summary relative risks were calculated using random-effects models. A total of 28 studies (27 publications) were included. Twenty-three prospective studies with >15 905 incident cases among 647 388 participants were included in the analysis of body mass index and heart failure incidence, and 4 studies were included for heart failure mortality. The summary relative risk for a 5-unit increment in body mass index was 1.41 (95% confidence interval, 1.34–1.47; I 2 =83%) for heart failure incidence and 1.26 (95% confidence interval, 0.85–1.87; I 2 =95%) heart failure mortality. Although the test for nonlinearity was significant ( P <0.0001), this appeared to be attributable to a threshold at a body mass index of ≈23 to 24 kg/m 2 ; however, there was evidence of increased risk even in the overweight body mass index range. The summary relative risk for a 10-cm increase in waist circumference was 1.29 (95% confidence interval, 1.21–1.37; I 2 =89%) and per 0.1-unit increase in waist-to-hip ratio was 1.29 (95% confidence interval, 1.13–1.47; I 2 =82%). Conclusion—: Overweight and obesity and abdominal adiposity are associated with increased risk of heart failure. Abstract : Supplemental Digital Content is available in the text.